Development of a Tool to Evaluate the Quality of Mentoring for Nurses (Medico Legal Update, 2019)
Background/Objectives: This study developed a tool to evaluate the quality of mentoring(QOM) for nurses and verified its validity and reliability before implementing a mentoring system as a strategy to manage them.Method/Statistical Analysis: One hundred twelve preliminary questions were derived from literature and the tool included 74 questions with a content validity at 0.75 or higher selected by an expert group. Ninety nine mentees participated in the prior survey and the main survey, respectively. Their general characteristics were analyzed using the SPSS Windows 18.0 program. The tool’s construct validity and internal consistency reliability were analyzed using factor analysis and Cronbach’s ? coefficient, respectively.Findings: The subjects of this study were 99 nurses who had participated in a mentoring system for new nurses as mentees in an advanced general hospital located in Seoul. The general characteristics of the subjects are as follows: The subjects’ average age was 24.8. Females accounted for 92.9% of the subject population. The subjects’ average clinical experience was 14.4 months. The final version of the tool to evaluate the quality of mentoring consisted of 32 questions. To examine the construct validity of the tool, an exploratory factor analysis was performed. The tool to evaluate the QOM was composed of three factors and five domains: the structure factor (mentoring program domain), the process factor (psychosocial function, career development function, and role model function domains), and the outcome factor (mentoring value domain). Cronbach’s ?, a measure of the tool’s internal consistency reliability, was 0.96.Improvements/Applications: This study developed a tool to comprehensively evaluate the quality of a mentoring program to apply an effective mentoring system and establish an efficient human resource management strategy in nursing